2021
DOI: 10.3126/jiom.v43i1.37469
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Carotid Endarterectomy in a Tertiary Center of Nepal: A Retrospective Study

Abstract: Introduction Carotid endarterectomy for carotid artery disease is one of the surgeries performed by vascular surgeons for carotid artery disease. The objective of this study is to describe the early and late outcome of the patient undergoing carotid endarterectomy and the association between the complication and comorbidities present previously in the patient. MethodsAll patients undergoing carotid endarterectomy at Manmohan Cardiothoracic Vascular and Transplant Centre between April 2010 to April 2020 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…A study from Pakistan reported that 15% of patients were not aware of a surgical option for carotid stenosis [18]. Our results were similar to that of few other studies in Asian countries, where the predominant presentation was with a stroke [12‒14, 19]. This is in contrast to the Western world wherein more than 50% of patients undergo CEA after a hemispheric or a retinal TIA [8‒11].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A study from Pakistan reported that 15% of patients were not aware of a surgical option for carotid stenosis [18]. Our results were similar to that of few other studies in Asian countries, where the predominant presentation was with a stroke [12‒14, 19]. This is in contrast to the Western world wherein more than 50% of patients undergo CEA after a hemispheric or a retinal TIA [8‒11].…”
Section: Discussionsupporting
confidence: 84%
“…However, randomized controlled trials (RCTs) include large volume centers with highly specialized surgeons and their results may not be replicable in all patient populations. While the majority of patients in the Western world undergo CEA even after a transient ischemic attack (TIA) [8][9][10][11], it is the reverse in low-and middle-income countries where CEA is done most often after a stroke [12][13][14] and tends to be delayed compared to the guideline recommended timing within 2 weeks. In this background, the application of these guidelines in low-and middle-income countries requires an understanding of the profile of patients who undergo carotid revascularization.…”
Section: Introductionmentioning
confidence: 99%